Efficacy of 2-Month Treatment With Cord Blood Serum Eye Drops in Ocular Surface Disease: An In Vivo Confocal Microscopy Study. Issue 8 (August 2017) - Giannaccare, Giuseppe; Buzzi, Marina; Fresina, Michela; Velati, Claudio; Versura, Piera
Abstract : Purpose: To investigate the morphological changes of corneal epithelium and subbasal nerves by in vivo confocal microscopy in patients with ocular surface disease (OSD) treated with cord blood serum (CBS) eye drops. Methods: Twenty patients with OSD (mean age 61.1 ± 12.6 years) were included in this prospective 1-arm study and treated with CBS eye drops for 2 months. Corneal sensitivity, Schirmer test score, breakup time, subjective symptoms [Ocular Surface Disease Index (OSDI) and Visual Analogue Scale (VAS)], and corneal staining were evaluated before (T0) and after (T1) treatment. In vivo confocal microscopy analyzed giant epithelial cells, subbasal nerve number and tortuosity, neuromas, beading, and dendritic cells (DCs) in the central cornea. Results: OSDI, Visual Analogue Scale, and Oxford grading values significantly decreased at T1 versus T0 (respectively, 44.1 ± 18.9 vs. 74.2 ± 13.9; 3.7 ± 1.5 vs. 8.9 ± 0.9; and 2.4 ± 1.1 vs. 3.3 ± 1.3; P < 0.0001), whereas corneal sensitivity, Schirmer test score, and breakup time significantly increased (respectively, 49.5 ± 2.6 vs. 47.9 ± 2.9; 3.2 ± 2.0 vs. 2.4 ± 2.2; 4.6 ± 3.1 vs. 3.8 ± 2.1; P < 0.0001). Corneal nerve morphology improved at T1 versus T0 with a higher total nerve number (3.4 ± 1.6 vs. 2.5 ± 1.6 per frame) and lower tortuosity (3.0 ± 0.7 vs. 3.5 ± 0.6) ( P < 0.01). The number of patients presenting with giant epithelial cells, beading, and neuromas decreased at T1. DC density did not change after treatment. The detection of neuromas and higher DC density at T0 were associated with greater OSDI reduction at T1 ( P < 0.001). Conclusions: CBS eye drops significantly improved corneal nerve morphology and subjective symptoms in patients with severe OSD. The presence of neuromas and higher dendritic cell density at baseline were associated with greater reduction of discomfort symptoms after treatment.